2017
DOI: 10.1089/ars.2016.6947
|View full text |Cite
|
Sign up to set email alerts
|

Stress-Induced ProteinS-Glutathionylation andS-Trypanothionylation in African Trypanosomes—A Quantitative Redox Proteome and Thiol Analysis

Abstract: Aims: Trypanosomatids have a unique trypanothione-based thiol redox metabolism. The parasite-specific dithiol is synthesized from glutathione and spermidine, with glutathionylspermidine as intermediate catalyzed by trypanothione synthetase. In this study, we address the oxidative stress response of African trypanosomes with special focus on putative protein S-thiolation.Results: Challenging bloodstream Trypanosoma brucei with diamide, H2O2 or hypochlorite results in distinct levels of reversible overall protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 78 publications
(149 reference statements)
3
22
0
Order By: Relevance
“…The reverse reaction, namely the reduction of mixed disulfides of GSH with proteins, is the primary function of glutaredoxins and Grx1 is not the exception (28). In the infective form of T. brucei, Grx1 accounts for about 40 -50% of the deglutathionylase activity measured in cell extracts (27), which was then confirmed by the slow reversion of protein S-thiolation in Grx1-KO parasites exposed to diamide (67). The current evidence shows that Grx1 does not function as a major protein oxidoreductase in the protection against oxidative stress (66, 67) but as key redox regulator of the activity of yet unknown partner(s) involved in parasite thermotolerance (27).…”
Section: Biological Implications Derived From Grx1 Kinetic Behavior Amentioning
confidence: 88%
See 1 more Smart Citation
“…The reverse reaction, namely the reduction of mixed disulfides of GSH with proteins, is the primary function of glutaredoxins and Grx1 is not the exception (28). In the infective form of T. brucei, Grx1 accounts for about 40 -50% of the deglutathionylase activity measured in cell extracts (27), which was then confirmed by the slow reversion of protein S-thiolation in Grx1-KO parasites exposed to diamide (67). The current evidence shows that Grx1 does not function as a major protein oxidoreductase in the protection against oxidative stress (66, 67) but as key redox regulator of the activity of yet unknown partner(s) involved in parasite thermotolerance (27).…”
Section: Biological Implications Derived From Grx1 Kinetic Behavior Amentioning
confidence: 88%
“…A recent study shows that Grx1 does not contribute to the overall protein S-thiolation of T. brucei (i.e. the level of protein-bound GSH was almost identical in WT and Grx1-deficient cells (67)). This is likely explained by the fact that Grx1 is rapidly oxidized to its disulfide by GSSG and that the glutathionylated intermediate could only be detected at low concentrations of GSSG.…”
Section: Biological Implications Derived From Grx1 Kinetic Behavior Amentioning
confidence: 99%
“…The level of free thiols, free thiols and disulfides and protein-bound thiols was determined as described previously [64] . Shortly, about 1 × 10 8 BS T. brucei were grown at 37 °C or 39 °C, washed with PBS and an aliquot was removed for counting.…”
Section: Methodsmentioning
confidence: 99%
“…Despite the absence of a classical glutathione system, trypanosomatids contain appreciable concentrations of free GSH as well as a repertoire of distinct Grxs [12] , [33] . Recently we showed that as response to exogenous and endogenous oxidative stresses, the mammalian bloodstream (BS) form of T. brucei can undergo protein S-glutathionylation and S-trypanothionylation [64] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation